Religious Character And Leadership Style of The Head of UPI Sumedang Futsal On Team Presentation (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to analyze the relationship between the religious character and democratic leadership style of the head of the Futsal Student Activity Unit (UKM Futsal) at UPI Sumedang on team performance. The research uses a quantitative method with a correlational design. Data were collected through questionnaires distributed to 30 active student members of UKM Futsal. The instruments used had been tested for validity and reliability in previous studies. The results of descriptive analysis showed high average scores for religious character, leadership style, and team performance. The normality and linearity tests confirmed that the data were normally distributed and had linear relationships. The Pearson correlation test and multiple regression analysis revealed a significant and positive relationship between religious character and democratic leadership style with team performance (R = 0.586, Sig. = 0.003). These findings indicate that the synergy between a strong moral foundation derived from religious values and a participatory leadership approach can enhance motivation, team cohesion, and overall achievement. This study contributes to the field of sports leadership by highlighting the importance of integrating ethical values and inclusive leadership practices in student sports organizations. Therefore, leadership development programs should emphasize not only technical competence but also religious and character education to produce effective and value-driven leaders.